2020
DOI: 10.1016/j.pacfin.2020.101296
|View full text |Cite
|
Sign up to set email alerts
|

Sovereign ratings and national culture

Abstract: Default by sovereign governments depends upon their willingness to default and the nation's capacity to pay. These are major factors considered by rating analysts and both may be affected by national culture. We hypothesise that ratings are related to culture and empirically examine the relation between culture and both levels and changes in sovereign ratings. Sovereign ratings have traditionally been modelled in terms of macroeconomic variables, rating outlook and rating history. Culture variables are signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 70 publications
(78 reference statements)
0
2
0
Order By: Relevance
“…Afonso et al (2007) show that, since the Asian crisis, international reserves have taken on greater importance. Recently, Dang and Partington (2020) have shown that culture has an impact on sovereign ratings and Fuchs and Gehring (2017) have found that culturally familiar countries have higher and similar ratings.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Afonso et al (2007) show that, since the Asian crisis, international reserves have taken on greater importance. Recently, Dang and Partington (2020) have shown that culture has an impact on sovereign ratings and Fuchs and Gehring (2017) have found that culturally familiar countries have higher and similar ratings.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, these factors relating to the agent's behavior need to be considered in the model describing the evolution of investment decisions. Xuan and Dang [1] analyzed herding behavior patterns under different stock portfolios and revealed the existence of herding behavior in particular industry. Zhang and Wang [2] employed the complex network method to investigate the correlation between herding behavior and the overconfidence behavior of investors.…”
Section: Introductionmentioning
confidence: 99%